2002
DOI: 10.1590/s0100-41582002000200004
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and translocation of nitrogen, phosphorus and calcium in soybean infected with Meloidogyne incognita and M. javanica

Abstract: Two soybean (Glycine max) cultivars were used in this study, Ocepar 4, rated as moderately resistant to Meloidogyne incognita race 3 but susceptible to M. javanica, and 'BR 16', susceptible to both nematodes. The effect of nematodes infection on the uptake and transport of N, P and Ca to the shoot was studied in plants growing in a split root system. The upper half was inoculated with 0, 3,000, 9,000 or 27,000 eggs/plant while the lower half received 15N, 32P or 45Ca. Infected plants showed an increase of root… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 10 publications
2
23
0
1
Order By: Relevance
“…However, the increases of the dry shoot mass and the fresh root mass were directly proportional to the inoculum level used in the experiment. Most likely, this is because nematodes cause several physiological disturbances in the plants, mainly in the roots, leading to the formation of new secondary roots (Carneiro et al, 2002). In addition, the growth of the aerial part tends to be proportional to the growth of the root system (Leskovar, 1998).…”
Section: Resultsmentioning
confidence: 99%
“…However, the increases of the dry shoot mass and the fresh root mass were directly proportional to the inoculum level used in the experiment. Most likely, this is because nematodes cause several physiological disturbances in the plants, mainly in the roots, leading to the formation of new secondary roots (Carneiro et al, 2002). In addition, the growth of the aerial part tends to be proportional to the growth of the root system (Leskovar, 1998).…”
Section: Resultsmentioning
confidence: 99%
“…Neither AMF nor nematodes appeared to influence the content of these nutrients in the aerial parts of alpinia plants. Carneiro et al (2002) observed that the quantity of Ca in the aerial parts of soy ( Glycine max (L.) Merr.) was not affected by the presence of M. incognita or M. javanica , and Jaizme-Vega et al (1997) obtained similar results in mycorrhized banana trees infected with M. incognita .…”
Section: Resultsmentioning
confidence: 99%
“…Feeding activities of nematodes interfere with plant physiological functions including photosynthesis and leading to a decline in growth criteria (Carneiro et al, 2002). The role of increasing level of nematode inoculum has been related to an increase in the formation of galls (Carneiro et al, 1999;Abrao and Mazzafera, 2001).…”
Section: B Effect Of Different Inoculum Levels Of M Javanica Eggs Omentioning
confidence: 99%